2010
DOI: 10.1007/s00420-010-0524-4
|View full text |Cite
|
Sign up to set email alerts
|

Bromide and N-acetyl-S-(n-propyl)-l-cysteine in urine from workers exposed to 1-bromopropane solvents from vapor degreasing or adhesive manufacturing

Abstract: This study shows that urinary Br(-) and AcPrCys are useful biomarkers of workers' 1-BP exposures using analyses sensitive enough to measure low exposure jobs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…The calculated metabolic constants are based on systemic concentrations of the 1-BP and can be used for risk assessment and dosimetry for other routes of exposure. Several studies have monitored urine metabolites from animals and humans occupationally exposed to 1-BP (Hanley et al, 2006(Hanley et al, , 2009(Hanley et al, , 2010Valentine et al, 2007). Further development of the PBPK model to include the compartment of the metabolites of 1-BP is undergoing.…”
Section: Discussionmentioning
confidence: 99%
“…The calculated metabolic constants are based on systemic concentrations of the 1-BP and can be used for risk assessment and dosimetry for other routes of exposure. Several studies have monitored urine metabolites from animals and humans occupationally exposed to 1-BP (Hanley et al, 2006(Hanley et al, , 2009(Hanley et al, , 2010Valentine et al, 2007). Further development of the PBPK model to include the compartment of the metabolites of 1-BP is undergoing.…”
Section: Discussionmentioning
confidence: 99%
“…This larger comprehensive study is beyond the scope of this short communication and will be reported in detail elsewhere [28,33]. The focus of this work was the development of the HPLC-MS procedure and its figures of merit.…”
Section: Methods Reproducibility Assay Sample Stability and Future Workmentioning
confidence: 99%
“…Field urine sample collection and detail has been described elsewhere by Hanley et al [28,33]. All urine was collected with appropriate human subject and IRB approvals.…”
Section: Urine Samplesmentioning
confidence: 99%
See 2 more Smart Citations